Bolsa Família: a process toward a Citizen's Basic Income in Brazil? (Revista Rupturas, 2025)
This article analyzes the Bolsa Família Program in Brazil, focusing on its evolution from the first version in 2003 to the current version in 2023. The study is based on a bibliographic, documentary, and field review to problematize the program's implementation as the largest income transfer program in Latin America. The role of Bolsa Família in the Brazilian social protection system is discussed, highlighting its contribution to the reduction of extreme poverty, albeit with a limited impact on social inequality. The analysis emphasizes the nature of conditional income transfers as a starting point for the construction of a Citizen's Basic Income, despite the limitations for its universalization and the absence of a clear plan for this process.
Keywords: Bolsa Família; Monetary Transfer; Poverty; Universal Basic Income